An miRNA-mRNA integrative analysis in human placentas and mice: role of the Smad2/miR-155-5p axis in the development of fetal growth restriction - Wu, Jia-Xing; Shi, Ming; Gong, Bao-Ming; Ji, Bao-Wei; Hu, Cheng-Chen; Wang, Gui-Cheng; Lei, Lei; Tang, Chao; Sun, Ling V.; Wu, Xiao-Hui; Wang, Xue (Frontiers in Bioengineering and Biotechnology, 2023)
The placenta, a source of peptides and steroid hormones, directly supports embryonic development. Functional disorder of the placenta is the principal cause of fetal growth restriction (FGR), usually cured with suitable clinical treatment and good nursing. However, some FGR mothers still give birth to small for gestational age (SGA) babies after treatment had failure. The ineffectiveness of treatment in such a group of patients confused physicians of obstetrics and gynecology. Recently, numerous studies examining changes in mRNA and miRNAs in placentas from women with pregnancy complications, including growth restriction. In this study, we performed a microRNA-messenger RNA integrative analysis of gene expression profiles obtained from Gene Expression Omnibus. Differentially expressed genes were screened and checked using quantitative polymerase chain reaction. miR-155-5p expression was upregulated (P = 0.001, fold-change = 2.275). Target genes of miR-155-5p were screened and enriched for Gene Ontology and Kyoto Encyclopedia of Genes and Genomes pathway analyses. Among the hub genes identified as key targets for miR-155-5p in fetal reprogramming, Smad2 was downregulated (P = 0.002, fold change = 0.426) and negatively correlated with miR-155-5p expression levels (r =－0.471, P <1.0 E – 04) in fetal-side placental tissues. The miR-155-5p mimic blocks Smad2 expression and suppresses villous trophoblast cell function (proliferation, migration, and invasion), indicating a close relationship with placental development. Luciferase assays further confirmed the targeting of miR-155-5p to Smad2. Furthermore, Smad2+/– heterozygote male mice were born small with low body weight (P = 0.0281) and fat composition (P = 0.013) in the 4th week post-natal. We provide the first evidence of the role of the Smad2/miR-155-5p axis in placental pathologies of FGR. Our findings elucidate the pathogenesis of FGR and provide new therapeutic targets.